Diagnostic Challenge of Adult-onset Type 1 Diabetes Mellitus in a Remote Hospital - Bryan Arista Hartono; Joshua Henrina; Doddy M Turmudzi (Majalah Kedokteran Bandung, 2023)
Type 1 Diabetes Mellitus (T1DM) is a chronic endocrinological disease due to an autoimmune process. The prevalence of T1DM is 9.5% worldwide, with the incidence of 15 out of 100,000 people, ranging from childhood to 40 years of age. Autoimmunity-related late-onset Diabetes Mellitus (DM) patients could be diagnosed as classic T1DM or latent autoimmune diabetes in adults (LADA). A 30-year-old male patient with unremarkable previous medical history was admitted to the emergency room with dyspnea for the last three days that was worsened six-hour before admission. Physical examinations showed a body Mass Index (BMI) of 18.75 kg/m2, irregular pulse, and Kussmaul breathing. The patient was diagnosed with diabetic ketoacidosis (DKA) on May 23, 2019. He was discharged with subcutaneous insulin pen injections. Two years later, he was readmitted with DKA due to discontinuing his treatment. He stated that the reason for stopping the insulin was because he was tired of injecting it. The patient was hospitalized and was discharged with oral antidiabetic agents to cope with his injection tiredness issue. One week later, the patient complained of dyspnea and was diagnosed with recurrent DKA. He was hospitalized and prescribed subcutaneous insulin. In this kind of situation, a diagnosis of LADA for patients presenting with DKA without prior history of DM in early adulthood needs to be considered. In contrast to the classic T1DM, the need for insulin occurs late in LADA. Affordable and widely available ancillary examinations are needed, including in remote hospitals. Finally, motivational support for patients is as important as the pharmacological treatment since lifelong insulin injections are needed.